2021
DOI: 10.31033/ijrasb.8.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Myristica fragrans (Jaiphal): A Significant Medicinal Herbal Plant

Abstract: The tradition of using herbal drugs and herbal remedies for treating human ailments is very old. From last few years, the demand of herbal remedies has been increased. Myristica fragrans Houtt, commonly known as nutmeg, is a very common spice, which is used around the world. It is described in almost each medicine system such as Ayurveda, Siddha, Unani and folk system. It has wide range of fixed oils and essential oils in it for example myristicin, safrole, myristic acid, trimyristicin, eugenol, elimicin and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The results indicated that the human gut's absorption of all flavonoid compounds was extensively investigated. Medications and other chemical substances that entered the body were eliminated by a transmembrane glycoprotein known as P-glycoprotein, which is involved in ATP binding [ 14 , 15 ]. The results of the study indicated that taxifolin, hesperidin, isoquercetin, myricetin, silibinin, and narirutin, which are nonsubstrate inhibitors of P-glycoprotein, exhibited either substrate or inhibitory properties toward P-glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the human gut's absorption of all flavonoid compounds was extensively investigated. Medications and other chemical substances that entered the body were eliminated by a transmembrane glycoprotein known as P-glycoprotein, which is involved in ATP binding [ 14 , 15 ]. The results of the study indicated that taxifolin, hesperidin, isoquercetin, myricetin, silibinin, and narirutin, which are nonsubstrate inhibitors of P-glycoprotein, exhibited either substrate or inhibitory properties toward P-glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
“…The main resource for discovering and developing a large number of new potential antiviral medicines are natural medicinal herbs that modulate flavonoids [ 12 , 13 ]. The group of phenyl benzopyrones, known as flavonoids, has a low molecular weight and many pharmacological effects, such as anti-inflammatory, antiviral, and antioxidant activities [ 14 , 15 ]. Flavonoids inhibit the release of viral particles from being executed, which disrupts viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…All the four humours in their correct quantity, quality, and ratio are responsible for regulating body function 20 . From this perspective the following drugs were prescribed, Elettaria cardamom 21 , Syzygium aromaticum 22 , Abies webbiana 23 , and Myristica fragrans 24 to help, correct and improve the digestive system. These drugs are also known to maintain the balance and the production of yellow bile from the liver.…”
Section: Su I Mizaj Har Maddimentioning
confidence: 99%
“…It is a tropical plant that is available in Malaysia, India, Indonesia, and South East Asia (Morsy 2016;Obranovic et al 2021). It was also mentioned in some literature to be a native plant from Banda Island in the Moluccas which is one of the regions in Eastern Indonesia and also important to note that almost half of the world's nutmeg is supplied from the country (Ibrahim et al 2020;Kumari et al 2021). Moreover, the bioactive compounds in nutmeg seeds including the oil and essential oil have been investigated for their potential application as antidiabetic (Pashapoor et al 2020), and in medical sciences (Ibrahim et al 2020;Weerakoon et al 2021).…”
Section: Determination Of Fatty Acids In Nutmeg Seed Oilmentioning
confidence: 99%